2007
DOI: 10.1097/qad.0b013e3282efb74b
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal mucosa as a reservoir of HIV-1 infection after successful HAART

Abstract: The presence of HIV-1 RNA in distal duodenal mucosa was evaluated in 44 HIV-1-positive patients. HIV-1 RNA was detected in gut tissue in antiretroviral-naive patients with high plasma viral loads, as well as in patients on HAART with plasma viral loads below the limit of detection and in patients on HAART with virological failure. The intestinal mucosa seems to serve as a reservoir poorly influenced by levels of plasma viral load or HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…We hope that our studies generate interest in the ts1 mouse as a model for HIV-1-induced thymic and intestinal infection and T cell death. Under conventional HAART therapy regimens, the intestine can serve as a viral reservoir, allowing gastrointestinal symptoms to continue despite control of viral load in the blood [50]. If GVT actually re-sets the redox tone in the ts1-infected mouse intestine, as it apparently does in the thymus [25], then repopulation of the intestinal T cell compartment could be possible, either from autologous bone marrow or allogeneic bone marrow or stem cell grafting.…”
Section: Discussionmentioning
confidence: 99%
“…We hope that our studies generate interest in the ts1 mouse as a model for HIV-1-induced thymic and intestinal infection and T cell death. Under conventional HAART therapy regimens, the intestine can serve as a viral reservoir, allowing gastrointestinal symptoms to continue despite control of viral load in the blood [50]. If GVT actually re-sets the redox tone in the ts1-infected mouse intestine, as it apparently does in the thymus [25], then repopulation of the intestinal T cell compartment could be possible, either from autologous bone marrow or allogeneic bone marrow or stem cell grafting.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of patients with acute infection showed that HIV DNA in the gut was significantly lower at Fiebig stage I than at Fiebig stages II to IV (79). The HIV DNA load in GALT declines after cART initiation (78) but does not disappear (150,158,163,164), and HIV DNA levels vary at different gut sites (151,(158)(159)(160)(161). Memory effector cells harbored the most HIV DNA in the ileum and rectum (161).…”
Section: Gut-associated Lymphoid Tissuementioning
confidence: 99%
“…The four animals had varying levels of pVL prior to antiretroviral therapy. We included animals with both low pVL and higher pVL (1) to assess decay of tissue reservoirs (i.e., the GALT), as it is known that even when pVLs are undetectable in peripheral blood, replicating virus is consistently found in tissues such as GALT, 3,16,25,26 and (2) to evaluate immune restoration and activation, because even in LTNP, gut immune CD4…”
Section: Discussionmentioning
confidence: 99%